2022
DOI: 10.1007/s12185-022-03470-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of epigenetics in T-cell lymphoma

Abstract: Malignant lymphomas are a group of diseases with epigenomic abnormalities fundamental to pathogenesis and pathophysiology. They are characterized by a high frequency of abnormalities related to DNA methylation regulators (DNMT3A, TET2, IDH2, etc.) and histone modifiers (EZH2, HDAC, KMT2D/MLL2, CREBBP, EP300, etc.). These epigenomic abnormalities directly amplify malignant clones. They also originate from a hematopoietic stem cell-derived cell lineage triggered by epigenomic changes. These characteristics are l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Deregulated expression and/or activity of these epigenetic writers, lead to genome-wide DNA and histone modification pattern alterations, modifying the chromatin structure, and thereby leading to cancer development. 56 Importantly, HDACs have become a promising therapeutic targets (see below) in the context of some TCLs such as CTCL, through their role in the silencing of different BCL-2 proapoptotic family members and in the regulation of autophagy. 57 (a) Loss-of-function mutations affecting epigenetic regulators such as the SET domain of the histone-lysine N-methyltransferase 2D (MLL2/KMT2D), CREB binding protein (CREBBP), and E1A binding protein 300 (EP300) genes, as well as activating mutations of the enhancer of zeste homolog 2 (EZH2) histone methyltransferase (HMT) gene and the overexpression of HDAC1/2/6 have been reported in B-cell lymphoma cases.…”
Section: Epigenetic Deregulations In B-and T-cell Lymphomamentioning
confidence: 99%
See 1 more Smart Citation
“…Deregulated expression and/or activity of these epigenetic writers, lead to genome-wide DNA and histone modification pattern alterations, modifying the chromatin structure, and thereby leading to cancer development. 56 Importantly, HDACs have become a promising therapeutic targets (see below) in the context of some TCLs such as CTCL, through their role in the silencing of different BCL-2 proapoptotic family members and in the regulation of autophagy. 57 (a) Loss-of-function mutations affecting epigenetic regulators such as the SET domain of the histone-lysine N-methyltransferase 2D (MLL2/KMT2D), CREB binding protein (CREBBP), and E1A binding protein 300 (EP300) genes, as well as activating mutations of the enhancer of zeste homolog 2 (EZH2) histone methyltransferase (HMT) gene and the overexpression of HDAC1/2/6 have been reported in B-cell lymphoma cases.…”
Section: Epigenetic Deregulations In B-and T-cell Lymphomamentioning
confidence: 99%
“…Deregulated expression and/or activity of these epigenetic writers, lead to genome-wide DNA and histone modification pattern alterations, modifying the chromatin structure, and thereby leading to cancer development. 56…”
Section: Introductionmentioning
confidence: 99%
“…The TME is the main source of extrinsic growth, and the survival signal provided by the TME’s non-neoplastic cells including different hematopoietic (myeloid, lymphoid) and non-hematopoietic cells is essential for T-lymphoma survival ( 35 37 ) ( Figure 1 ). The source T-cell variant from which the tumorigenic T cell derives significantly dictates the composition of the TME ( 39 , 42 , 53 , 54 ). As in the case of AITL (angio-immunoblastic T-cell lymphoma), the overexpression of follicular T helper cells (Tfh) associated with cell surface receptors (ICOS, PD-1, and CXCR-5) along with BCL-6 established that AITL tumorigenic cells originated from Tfh cells.…”
Section: Tumor Microenvironment Of T-cell Lymphoma and The Role Of Cy...mentioning
confidence: 99%
“…These observations suggested that the cell of origin is a major factor behind the composition of the TME in developing T-cell lymphomas and established the importance of TCR-mediated signaling aided by co-stimulatory and cytokine signaling in transcriptional and posttranscriptional regulations of these master transcription factors ( 38 ). These signaling alternations subsequently result in the development of a specific TME, which is evident by the homology between the receptor profile of T-lymphoma cells and the T cells’ source of origin subtypes ( 53 , 54 ). Subsequently, the constituents of the TME in turn influence the availability of ligands and cytokines which drive the T-cell lymphoma growth proliferation and survival.…”
Section: Tumor Microenvironment Of T-cell Lymphoma and The Role Of Cy...mentioning
confidence: 99%
“…Disruption of DNA methylation and histone modifications has become a hallmark of these diseases and the basis for epigenetically targeted therapies [ 88 ]. As the understanding of epigenetic complexity continues to deepen, it has been found that mutations in these epigenetic regulators have a global impact on lymphoma development and drug sensitivity, and the ability to silence multiple genes at the same time through the regulation of a large number of genes leads to polygenic drug resistance [ 89 , 90 ].…”
Section: Introductionmentioning
confidence: 99%